Brain histiocytosis with precocious puberty and growth hormone deficiency at early childhood – A case report - Katanić, Dragan; Kolarović, Jovanka; Grujičić, Danica; Skender Gazibara, Milica; Knežević Pogančev, Marija; Koprivšek, Katarina; Vlaški, Jovan; Vorgučin, Ivana; Katanić, Jasmina (Vojnosanitetski pregled, 2021)
Introduction. Langerhans Cell Histiocytosis (LCH) is a rare chronic granulomatous, usually multisystem disease of elusive etiology, with peak incidence in early childhood and slow progressing course. Isolated brain histiocytosis is a very rare condition and neurological finding does not correlate with the extent of space-occupying anatomical lesions and degenerative changes. Case report. A girl, age 2.5 years was presented with diabetes insipidus and nearly fatal full spectrum isolated brain histiocytosis. Brain magnetic resonance imaging (MRI) showed multiple nodules with perifocal edema, the most prominent in the projection of the hypothalamus/pituitary and the stalk and in the region of the pineal gland. Identical nodules were present in both caudate nucleus and putamen, left insular subcortex, both temporal lobes, tegmental area of the midbrain, central part of pons and medulla, both cerebellar hemispheres and leptomeningeal membranes. The pattern resembled snow balls and flakes. Biopsy showed positivity for vimentin, S-100, CD-68 and CD1a markers. Treatment protocol LCH-III was not successful and a salvage treatment was refused by parents. She appeared again at the age of 7 with growth deceleration and fully developed precocious puberty. The control MRI of the brain revealed similar nodules in certain regression. Due to central precocious puberty, treatment with luteinizing hormone–releasing hormone (LH-RH) analogue was introduced. School performance was mediocre with cocktail-party effect behavior and slower speech. Conclusion. Brain histiocytosis is potentially fatal disease with chronic, variable, slowly progressive course and unpredictable responses to treatment protocols.
Keywords: histocytosis; brain; diagnosis; diabetes insipidus; drug therapy; treatment outcome